2019
DOI: 10.1080/14779072.2019.1627874
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for cardiopulmonary exercise testing in healthy subjects – an updated systematic review

Abstract: Introduction: Reference values for cardiopulmonary exercise testing (CPET) parameters provide the comparative basis for answering important questions concerning the normalcy of exercise responses in patients, and significantly impacts the clinical decision-making process. Areas covered: The aim of this study was to provide an updated systematic review of the literature on reference values for CPET parameters in healthy subjects across the life span. A systematic search in MEDLINE, Embase, and PEDro databases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
(53 reference statements)
2
55
1
Order By: Relevance
“…In contrast to past studies, [8,10] which have established that the absolute value of VO2/kg can serve as a survival predictor, our study highlighted the importance of the difference between the predicted and observed oxygen consumption. Typically, the maximal oxygen consumption in a healthy person can be predicted on the basis of age, sex, body height, and body weight, [41] and older women demonstrate lower oxygen consumption and older male patients with IPF demonstrate higher mortality. [25] Therefore, using the absolute value of VO2/kg instead of FAI in female patients with IPF could have the potential hazard of overestimating mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to past studies, [8,10] which have established that the absolute value of VO2/kg can serve as a survival predictor, our study highlighted the importance of the difference between the predicted and observed oxygen consumption. Typically, the maximal oxygen consumption in a healthy person can be predicted on the basis of age, sex, body height, and body weight, [41] and older women demonstrate lower oxygen consumption and older male patients with IPF demonstrate higher mortality. [25] Therefore, using the absolute value of VO2/kg instead of FAI in female patients with IPF could have the potential hazard of overestimating mortality.…”
Section: Discussionmentioning
confidence: 99%
“…More males than females were included in these two studies, with the second including male participants only (Hansen et al, 1984). A recently updated systematic review showed that, in studies establishing CPET reference values in healthy adults, females are underrepresented and account for 38% of the total number of included study participants (Takken et al, 2019). Although an increasing number of hospitals in the UK use CPET to assess surgical risk, separate reference values for males and females have not been reported in recent perioperative CPET publications (Levett et al, 2018;Reeves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(11), and Takken et al(12) published two systematic reviews in 2014 and 2019, where they studied refer-VO 2 max in females…”
mentioning
confidence: 99%